Computer-assisted Learning of Croatian Orthography concerning the YAT reflex (CAL-COR) - Boras, Damir (Array, 2005)
The aim of this paper is to present two phases in constructing the Croatian orthography learning system concerning the YAT reflex as well as its final form. During these two phases, we compared three different models of rules concerning the YAT reflex - a basic, an intermediate and an advanced one. We also compared two different approaches for learning the yat reflex - an introduction-deductive and an inductive one. All the data gathered during our research helped us in constructing a complete, powerful learning tool